Narrative Potential of Picture-Book Apps: A Media- and Interaction-Oriented Study - Müller-Brauers, Claudia; Miosga, Christiane; Fischer, Silke; Maus, Alina; Potthast, Ines (Frontiers in Psychology, 2020)
Digital literature is playing an increasingly important role in children’s everyday lives and opening up new paths for family literacy and early childhood education. However, despite positive effects of electronic books and picture-book apps on vocabulary learning, early writing, or phonological awareness, research findings on early narrative skills are ambiguous. Particularly, there still is a research gap regarding how app materiality affects children’s story understanding. Thus, based on the ViSAR model for picture-book app analysis and data stemming from 12 digital reading dyads containing German monolingual 2- to 3-year-olds and their caregivers this study assessed the narrative potential of a commercial picture-book app and how this is used in interaction. Results of the media analysis showed that the app provides a high number of narrative animations. These animations could be used interactively to engage the child in the story. However, results of the interaction analysis showed that adult readers do not exploit this potential due to their strong concentration on operative prompts and instructions. Furthermore, an explorative analysis of the relation between adults’ utterances and children’s story comprehension provided preliminary indicators regarding how the length of reading duration and the number of utterances might relate to children´s understanding of the story. Findings and methodological limitations of the study are discussed and combined didactically with practical recommendations on how to use narrative animations in interaction effectively.